Perfil de ácidos graxos em batatas Chips comercializadas em são José do Rio Preto - Brasil - Jorge, Neuza [UNESP]; Oliveira, Marcel de Campos [UNESP]; Luzia, Débora Maria Moreno [UNESP] (My University, 2010)
The objective this study was to evaluate the fatty acids profile of samples of chips potato marketed in the city of São Jose do Rio Preto-SP. We collected samples of 10 brands of chips potato, obtained from 3 different batches. The fatty acids profile was obtained by gas chromatography, with peak identified by retention times with standards of methyl esters and the results calculated and expressed as g/100g of the sample. The fatty acids profile in chips potatoes from different brands were on average 39.22% for saturated fatty acids, 39.64% for monounsaturated, 18.60% for polyunsaturated and 2.43% for trans fatty acids.

O objetivo deste trabalho foi avaliar o perfil de ácidos graxos de amostras de batatas chips comercializadas na cidade de São José do Rio PretoSP. Foram coletadas amostras de 10 marcas de batatas chips, obtidas de 3 lotes diferentes. O perfil de ácidos graxos foi obtido por cromatografia gasosa, sendo os picos identificados por tempos de retenção com padrões de ésteres metílicos e os resultados calculados e expressos em g/100g da amostra. O perfil de ácidos graxos determinados nas batatas chips provenientes de diferentes marcas foi, em média, 39,22% para ácidos graxos saturados, 39,64% para monoinsaturados, 18,60% para poliinsaturados e 2,43% para ácidos graxos trans.
Fatty Acids Profile in Chips Potato Marketed in the City of São José do Rio Preto, SP, Brazil
Keywords: Batatas chips; Ácidos graxos; Cromatografia gasosa; Chips potatoes; Fatty acids; Gas chromatography